Penggunaan Model Pembelajaran Think Pair Share Berbantuan Media Video Animasi Dilengkapi LKPD Anagram Untuk Meningkatkan Kognitif dan Afektif Siswa Kelas IX SMP Negeri 1 Waingapu: (The Use of the Think Pair Share Learning Model Assisted by Animated Video Media Equipped with Anagram LKPD to Improve the Cognitive and Affective Skills of Grade IX Students of SMP Negeri 1 Waingapu) - Pawolung, Rikardo Maki; Ina, Anita Tamu; Tamaela, Kevin Andrea (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2026)
The low science learning outcomes of grade IX B students at SMP Negeri 1 Waingapu are caused by the learning process which is still teacher-centered (conventional), the lack of use of interactive media, and the low active participation of students in understanding abstract concepts. This is evidenced by pre-cycle data where only 19% to 25.8% of students achieved the Minimum Completion Criteria (KKM). This study aims to improve students' cognitive and affective learning outcomes through the implementation of the Think Pair Share (TPS) cooperative learning model assisted by animated video media and equipped with Anagram LKPD. This type of research is Classroom Action Research (CAR) with the Kemmis & McTaggart model. The research subjects were 31 grade IX-B students of SMP Negeri 1 Waingapu. The instruments used included cognitive learning outcome tests and affective observation sheets. The results showed a significant increase in each cycle. In the cognitive domain, the average score increased from 56.77 in the pre-cycle to 64.19 in cycle I, and reached 75.48 in cycle II. The percentage of cognitive classical completion increased from 25.8% (pre-cycle) to 51.61% (cycle I) and reached 90.32% in cycle II. In the affective domain, the percentage of student achievement increased from 19.35% (less category) in the pre-cycle, to 70% (sufficient category) in cycle I, and reached 93.54% (very good category) in cycle II. Abstrak. Rendahnya hasil belajar IPA siswa kelas IX B di SMP Negeri 1 Waingapu yang disebabkan oleh proses pembelajaran yang masih berpusat pada guru (konvensional), kurangnya penggunaan media interaktif, serta rendahnya partisipasi aktif siswa dalam memahami konsep-konsep abstrak. Hal ini dibuktikan dengan data pra-siklus di mana hanya 19% hingga 25,8% siswa yang mencapai Kriteria Ketuntasan Minimal (KKM). Penelitian ini bertujuan untuk meningkatkan hasil belajar kognitif dan afektif siswa melalui penerapan model pembelajaran kooperatif tipe Think Pair Share (TPS) yang berbantuan media video animasi dan dilengkapi LKPD Anagram. Jenis penelitian ini adalah Penelitian Tindakan Kelas (PTK) dengan model Kemmis & McTaggart. Subjek penelitian adalah 31 siswa kelas IX-B SMP Negeri 1 Waingapu. Instrumen yang digunakan meliputi tes hasil belajar kognitif dan lembar observasi afektif. Hasil penelitian menunjukkan adanya peningkatan yang signifikan pada setiap siklus. Pada ranah kognitif, nilai rata-rata meningkat dari 56,77 pada pra-siklus menjadi 64,19 pada siklus I, dan mencapai 75,48 pada siklus II. Persentase ketuntasan klasikal kognitif meningkat dari 25,8% (pra-siklus) menjadi 51,61% (siklus I) dan mencapai 90,32% pada siklus II. Pada ranah afektif, persentase ketercapaian siswa meningkat dari 19,35% (kategori kurang) pada pra-siklus, menjadi 70% (kategori cukup) pada siklus I, dan mencapai 93,54% (kategori sangat baik) pada siklus II.